VITAMIN C DEFICIENCY IN CHILDREN WITH AUTISM SPECTRUM DISORDER - Raman, Pappathy; Shukor, Intan Nor Chahaya; Chia, Goh Sze; Zina'Ali, Nazirah Binti (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Avoidant/restrictive food intake disorder (ARFID) is common in individuals with autism. Micronutrients deficiencies should be considered in any physical illness. RESULTS We are reporting 2 patients with autism with Vitamin C deficiency. Case A, 9 years old boy, born prematurely 34 weeks with underlying autistic spectrum disorder at 4 years old. He presented with bilateral left lower limb pain since mid June 2020, at 8 years old associated with fever, anorexia and weight loss. Mother reported child is having difficulty with mobilization, refused to walk and required wheelchair. Parents assumed child has pain over his hip and knee due to limitation of his language. Initial diagnosis of Juvenile Rheumatoid arthritis was made and patient was referred to Rheumatologist Hospital Selayang. Vitamin C deficiency was suspected due to corkscrew hair. He has subperiosteal hemorrhage with bilateral knee fixed flexion deformity. He was treated with prednisolone tapering dose over 2 months, Ibuprofen, Multivitamin, Vitamin C and syrup FAC and knee splint. He started walking again after one month of treatment with full recovery after 3 months. Case B, 8 years old boy with underlying autistic spectrum disorder since 5 years old. He presented with bilateral thigh pain since April 2021 associated with difficulties in mobilization. He was treated for reactive arthritis and completed IV cloxacillin for 5 days with regular analgesic and physiotherapy. Vitamin C deficiency was suspected and treated with oral vitamin C. Initial Vitamin C level was low, <5 (normal 28-120). He started walking again after 3 weeks of treatment in June 2021. CONCLUSION Micro nutrient deficiencies such as Vitamin C should be considered in Autistic Spectrum Disorder children presenting with musculoskeletal pain.